Analisis keamanan Learning Management System (LMS) moodle dengan metode vulnerability scanning - Rahma, Diah Ayu; Firhah, Fina Maslahatul; Yaqin, Muhammad Ainul (Maliki Interdisciplinary Journal, 2024)
The Learning Management System (LMS) is a crucial e-learning platform for managing online education. One popular LMS used today is Moodle, which is open source and offers various customizable features to meet users’ needs. Security is a critical aspect of LMS because it stores sensitive data such as user information and learning materials. This research aims to analyze the security of Moodle using the Vulnerability Scanning method with OWASP-ZAP tools. The analysis include identifying security vulnerabilities, assessing their severity, and comparing them with other versions of the Moodle LMS. Recommendations for enhancing Moodle’s security will also be provided. This research targets Moodle administrators, security practitioners, and researchers in the field of information security. The expected outcomes of this research are to raise awareness of the importance of security in LMS, provide guidance for conducting vulnerability scanning on Moodle, and assist administrators in identifying and addressing potential security vulnerabilities in the Moodle platform.